Analisis Kualitas Pelayanan dengan Metode Student Satisfaction Inventory (SSI) di STIKes Persada Husada Indonesia - Elwindra Elwindra (Jurnal Persada Husada Indonesia, 2014)
With the intense level of competition between universities, Persada Husada Indonesia College of Health Sciences (STIKes PHI) are one of the many educational institutions in need in improving the quality of our educational services. It is necessary to measure and analyze the quality of education services provided by STIKes PHI, therefore appropriate steps can be taken to improve the services quality. The method that was used in this study was the Student Satisfaction Inventory (SSI) method which contained 12 dimensions of quality educational services. Each dimension was measured with both level of importance and level of satisfaction and analyzed by the technique of Importance Performance Analysis. An amount of 196 students was chosen as respondent for this study, and choosed based on stratified random sampling method. This research noted that STIKes PHI must prioritize in improving their efforts and quality of care to the factors that were included in Dimension: Academic Services (AS), Concern For the Individual (CFI), and Instructional Effectiveness (IE). The main concerns that were affecting student satisfaction lies in: class schedulling, library staff services, library facilities, computer lab facilities and services, promoting information, classes facilities and comfort, and responses to student complaints. STIKes PHI were advised to create improvements in its service dimensions which was included in priority dimensions, and continues to perform research service quality regularly, therefore the students expectations can be satisfy with efficiency and effectiveness.